2020
DOI: 10.3389/fsurg.2020.554382
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the Treatment of Lumbar Disc Degeneration: The Value Proposition for a Cell-Based Therapy, Immunomodulatory Properties of Discogenic Cells and the Associated Clinical Evaluation Strategy

Abstract: Low back pain (LBP) is a serious medical condition that affects a large percentage of the population worldwide. One cause of LBP is disc degeneration (DD), which is characterized by progressive breakdown of the disc and an inflamed disc environment. Current treatment options for patients with symptomatic DD are limited and are often unsuccessful, so many patients turn to prescription opioids for pain management in a time when opioid usage, addiction, and drug-related deaths are at an all-time high. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…While we used aggrecan production to guide our CFD models, other parameters could be used in the future as well. We have demonstrated that other molecules, such as collagen and anti-inflammatory molecules are also relevant to the mode of action of Discogenic Cells in treating lumbar disc degeneration [ 12 , 32 ]. Further work is needed to evaluate these potency measures in the context of transitioning to a STR and scaling into larger volumes.…”
Section: Discussionmentioning
confidence: 99%
“…While we used aggrecan production to guide our CFD models, other parameters could be used in the future as well. We have demonstrated that other molecules, such as collagen and anti-inflammatory molecules are also relevant to the mode of action of Discogenic Cells in treating lumbar disc degeneration [ 12 , 32 ]. Further work is needed to evaluate these potency measures in the context of transitioning to a STR and scaling into larger volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Discogenic cells are progenitor cells originating from adult human intervertebral disc tissue, specifically from the nucleus pulposus tissue, and have a notochordal origin [ 57 ]. These cells exhibit a multipotency for mesenchymal lineage differentiation [ 58 ] which could suggest a similar phenotype to MSCs, namely no ACE2 and TMPRSS2 expression and no susceptibility to coronavirus infection [ 50 , 51 ].…”
Section: Non-blood Derived Productsmentioning
confidence: 99%
“…These treatments may involve medications such as nonsteroidal anti‐inflammatory drugs (NSAIDs), which can address acute symptoms but carry the risk of increased internal bleeding during long‐term use 16 . For more severe symptoms, opioid‐based medications may be prescribed, 17 but they pose a serious risk of addiction, exacerbating the opioid epidemic and associated morbidities 18–21 . Where conservative treatments do not appear to modify disease progression, surgical interventions such as spinal fusion or total disc arthroplasty may be employed, but these fail to preserve disc structure or mechanical function long‐term and may result in progression of IVDD in adjacent levels 15 .…”
Section: Introductionmentioning
confidence: 99%
“…16 For more severe symptoms, opioid‐based medications may be prescribed, 17 but they pose a serious risk of addiction, exacerbating the opioid epidemic and associated morbidities. 18 , 19 , 20 , 21 Where conservative treatments do not appear to modify disease progression, surgical interventions such as spinal fusion or total disc arthroplasty may be employed, but these fail to preserve disc structure or mechanical function long‐term and may result in progression of IVDD in adjacent levels. 15 Therefore, there is a significant clinical need for improved treatment options for patients suffering from IVDD and LBP that directly target the underlying causes.…”
Section: Introductionmentioning
confidence: 99%